The Future of the Public's Health in the 21st Century - Institute of Medicine (The National Academies Press, 2003)
The anthrax incidents following the 9/11 terrorist attacks put the spotlight on the nation's public health agencies, placing it under an unprecedented scrutiny that added new dimensions to the complex issues considered in this report. The Future of the Public's Health in the 21st Century reaffirms the vision of Healthy People 2010, and outlines a systems approach to assuring the nation's health in practice, research, and policy. This approach focuses on joining the unique resources and perspectives of diverse sectors and entities and challenges these groups to work in a concerted, strategic way to promote and protect the public's health. Focusing on diverse partnerships as the framework for public health, the book discusses: The need for a shift from an individual to a population-based approach in practice, research, policy, and community engagement. The status of the governmental public health infrastructure and what needs to be improved, including its interface with the health care delivery system. The roles nongovernment actors, such as academia, business, local communities and the media can play in creating a healthy nation. Providing an accessible analysis, this book will be important to public health policy-makers and practitioners, business and community leaders, health advocates, educators and journalists.
Keywords: Health and Medicine

Health Professions Education: A Bridge to Quality - Institute of Medicine (The National Academies Press, 2003)
The Institute of Medicine study Crossing the Quality Chasm (2001) recommended that an interdisciplinary summit be held to further reform of health professions education in order to enhance quality and patient safety. Health Professions Education: A Bridge to Quality is the follow up to that summit, held in June 2002, where 150 participants across disciplines and occupations developed ideas about how to integrate a core set of competencies into health professions education. These core competencies include patient-centered care, interdisciplinary teams, evidence-based practice, quality improvement, and informatics. This book recommends a mix of approaches to health education improvement, including those related to oversight processes, the training environment, research, public reporting, and leadership. Educators, administrators, and health professionals can use this book to help achieve an approach to education that better prepares clinicians to meet both the needs of patients and the requirements of a changing health care system.
Keywords: Education; Health and Medicine

Ensuring Environmental Health in Postindustrial Cities: Workshop Summary - Institute of Medicine (The National Academies Press, 2003)
the Institute of Medicine Roundtable on Environmental Health Science, Research, and Medicine held a regional workshop in Pittsburgh, Pennsylvania, on March 13, 2003. This workshop was a continued outgrowth from the Roundtable's first workshop when its members realized that the challenges facing those in the field of environmental health could not be addressed without a new definition of environmental health--one that incorporates the natural, built, and social environment. The Roundtable realized that the industrial legacy is not unique to Pittsburgh. Other cities around the world have seen their industries disappear, and it is only a matter of time before some of the Pittsburghs of today, such as Wuhan, China, (a sister city) will need to address similar problems. One goal for this IOM Environmental Health Roundtable Workshop is to extract lessons from Pittsburgh's experience in addressing the post-industrial challenge, distilling lessons that might be useful elsewhere.
Keywords: Environment and Environmental Studies; Health and Medicine

Informing the Future: Critical Issues in Health: Second Edition - Institute of Medicine (The National Academies Press, 2003)

Microbial Threats to Health: Emergence, Detection, and Response - Institute of Medicine (The National Academies Press, 2003)
Infectious diseases are a global hazard that puts every nation and every person at risk. The recent SARS outbreak is a prime example. Knowing neither geographic nor political borders, often arriving silently and lethally, microbial pathogens constitute a grave threat to the health of humans. Indeed, a majority of countries recently identified the spread of infectious disease as the greatest global problem they confront. Throughout history, humans have struggled to control both the causes and consequences of infectious diseases and we will continue to do so into the foreseeable future. Following up on a high-profile 1992 report from the Institute of Medicine, Microbial Threats to Health examines the current state of knowledge and policy pertaining to emerging and re-emerging infectious diseases from around the globe. It examines the spectrum of microbial threats, factors in disease emergence, and the ultimate capacity of the United States to meet the challenges posed by microbial threats to human health. From the impact of war or technology on disease emergence to the development of enhanced disease surveillance and vaccine strategies, Microbial Threats to Health contains valuable information for researchers, students, health care providers, policymakers, public health officials. and the interested public.
Keywords: Health and Medicine

Gulf War and Health: Volume 2: Insecticides and Solvents - Institute of Medicine (The National Academies Press, 2003)
Gulf War and Health, Volume 2, is the second in a series of congressionally-mandated studies by the Institute of Medicine that provides a comprehensive assessment of the available scientific literature on potential health effects of exposure to certain biological, chemical, and environmental agents associated with the Gulf War. In this second study, the committee evaluated the published, peer-reviewed literature on exposure to insecticides and solvents thought to have been present during the 1990-1991 war. Because little information exists on actual exposure levels – a critical factor when assessing health effects – the committee could not draw specific conclusions about the health problems of Gulf War veterans. However, the study found some evidence, although usually limited, to link specific long-term health outcomes with exposure to certain insecticides and solvents. The next phase of the series will examine the literature on potential health effects associated with exposure to selected environmental pollutants and particulates, such as oil-well fires and jet fuels.
Keywords: Health and Medicine; Environment and Environmental Studies

Preparing for the Psychological Consequences of Terrorism: A Public Health Strategy - Institute of Medicine (The National Academies Press, 2003)
The Oklahoma City bombing, intentional crashing of airliners on September 11, 2001, and anthrax attacks in the fall of 2001 have made Americans acutely aware of the impacts of terrorism. These events and continued threats of terrorism have raised questions about the impact on the psychological health of the nation and how well the public health infrastructure is able to meet the psychological needs that will likely result. Preparing for the Psychological Consequences of Terrorism highlights some of the critical issues in responding to the psychological needs that result from terrorism and provides possible options for intervention. The committee offers an example for a public health strategy that may serve as a base from which plans to prevent and respond to the psychological consequences of a variety of terrorism events can be formulated. The report includes recommendations for the training and education of service providers, ensuring appropriate guidelines for the protection of service providers, and developing public health surveillance for preevent, event, and postevent factors related to psychological consequences.
Keywords: Conflict and Security Issues; Behavioral and Social Sciences

Initial Steps in Rebuilding the Health Sector in East Timor - National Research Council (The National Academies Press, 2003)
In May 2002 Timor Leste (East Timor) emerged as a new nation after centuries of foreign rule and decades of struggle for independence. Its birth was a painful one; a United Nations-brokered Popular Consultation in August 1999, in which an overwhelming majority of the people opted for independence, was followed by several weeks of vengeful violence, looting, and destruction by pro-Indonesia militias. It left the territory and all of its essential services devastated. In this context, the United Nations Transitional Administration in East Timor (UNTAET), with the country's leaders and people and many other partners, set about restoring order and services, building a government structure, and preparing for independence. This paper summarizes the rehabilitation and development of the health sector from early 2000 to the end of 2001.
Keywords: Behavioral and Social Sciences

Occupational Health and Safety in the Care and Use of Nonhuman Primates - National Research Council (The National Academies Press, 2003)
The field of occupational health and safety constantly changes, especially as it pertains to biomedical research. New infectious hazards are of particular importance at nonhuman-primate facilities. For example, the discovery that B virus can be transmitted via a splash on a mucous membrane raises new concerns that must be addressed, as does the discovery of the Reston strain of Ebola virus in import quarantine facilities in the U.S. The risk of such infectious hazards is best managed through a flexible and comprehensive Occupational Health and Safety Program (OHSP) that can identify and mitigate potential hazards. Occupational Health and Safety in the Care and Use of Nonhuman Primates is intended as a reference for vivarium managers, veterinarians, researchers, safety professionals, and others who are involved in developing or implementing an OHSP that deals with nonhuman primates. The book lists the important features of an OHSP and provides the tools necessary for informed decision-making in developing an optimal program that meets all particular institutional needs.
Keywords: Biology and Life Sciences; Agriculture

Frontiers in Agricultural Research: Food, Health, Environment, and Communities - National Research Council (The National Academies Press, 2003)
This report is a congressionally mandated review of the US Department of Agriculture’s Research, Education, and Economics (REE) mission area, the main engine of publicly funded agricultural research in the United States. A changing social and scientific context of agriculture requires a new vision of agricultural research -- one that will support agriculture as a positive economic, social, and environmental force. REE is uniquely positioned to advance new research frontiers in environment, public health, and rural communities. The report recommends that REE be more anticipatory and strategic in its use of limited resources and guide and champion new directions in research.
Keywords: Agriculture

Who Will Keep the Public Healthy?: Educating Public Health Professionals for the 21st Century - Institute of Medicine (The National Academies Press, 2003)
Bioterrorism, drug--resistant disease, transmission of disease by global travel . . . there’s no shortage of challenges facing America’s public health officials. Men and women preparing to enter the field require state-of-the-art training to meet these increasing threats to the public health. But are the programs they rely on provide the high caliber professional training they require? Who Will Keep the Public Healthy? provides an overview of the past, present, and future of public health education, assessing its readiness to provide the training and education needed to prepare men and women to face 21st century challenges. Advocating an ecological approach to public health, the Institute of Medicine examines the role of public health schools and degree--granting programs, medical schools, nursing schools, and government agencies, as well as other institutions that foster public health education and leadership. Specific recommendations address the content of public health education, qualifications for faculty, availability of supervised practice, opportunities for cross--disciplinary research and education, cooperation with government agencies, and government funding for education. Eight areas of critical importance to public health education in the 21st century are examined in depth: informatics, genomics, communication, cultural competence, community-based participatory research, global health, policy and law, and public health ethics. The book also includes a discussion of the policy implications of its ecological framework.
Keywords: Health and Medicine

Key Capabilities of an Electronic Health Record System: Letter Report - Institute of Medicine (The National Academies Press, 2003)
Commissioned by the Department of Health and Human Services, Key Capabilities of an Electronic Health Record System provides guidance on the most significant care delivery-related capabilities of electronic health record (EHR) systems. There is a great deal of interest in both the public and private sectors in encouraging all health care providers to migrate from paper-based health records to a system that stores health information electronically and employs computer-aided decision support systems. In part, this interest is due to a growing recognition that a stronger information technology infrastructure is integral to addressing national concerns such as the need to improve the safety and the quality of health care, rising health care costs, and matters of homeland security related to the health sector. Key Capabilities of an Electronic Health Record System provides a set of basic functionalities that an EHR system must employ to promote patient safety, including detailed patient data (e.g., diagnoses, allergies, laboratory results), as well as decision-support capabilities (e.g., the ability to alert providers to potential drug-drug interactions). The book examines care delivery functions, such as database management and the use of health care data standards to better advance the safety, quality, and efficiency of health care in the United States.
Keywords: Computers and Information Technology

Unequal Treatment: Confronting Racial and Ethnic Disparities in Health Care - Institute of Medicine (The National Academies Press, 2003)
Racial and ethnic disparities in health care are known to reflect access to care and other issues that arise from differing socioeconomic conditions. There is, however, increasing evidence that even after such differences are accounted for, race and ethnicity remain significant predictors of the quality of health care received. In Unequal Treatment, a panel of experts documents this evidence and explores how persons of color experience the health care environment. The book examines how disparities in treatment may arise in health care systems and looks at aspects of the clinical encounter that may contribute to such disparities. Patients' and providers' attitudes, expectations, and behavior are analyzed. How to intervene? Unequal Treatment offers recommendations for improvements in medical care financing, allocation of care, availability of language translation, community-based care, and other arenas. The committee highlights the potential of cross-cultural education to improve provider-patient communication and offers a detailed look at how to integrate cross-cultural learning within the health professions. The book concludes with recommendations for data collection and research initiatives. Unequal Treatment will be vitally important to health care policymakers, administrators, providers, educators, and students as well as advocates for people of color.
Keywords: Health and Medicine

Fostering Rapid Advances in Health Care: Learning from System Demonstrations - Institute of Medicine (The National Academies Press, 2003)
In response to a request from the Secretary of the Department of Health and Human Services, the Institute of Medicine convened a committee to identify possible demonstration projects that might be implemented in 2003, with the hope of yielding models for broader health system reform within a few years. The committee is recommending a substantial portfolio of demonstration projects, including chronic care and primary care demonstrations, information and communications technology infrastructure demonstrations, health insurance coverage demonstrations, and liability demonstrations. As a set, the demonstrations address key aspects of the health care delivery system and the financing and legal environment in which health care is provided. The launching of a carefully crafted set of demonstrations is viewed as a way to initiate a "building block" approach to health system change.
Keywords: Health and Medicine

Priority Areas for National Action: Transforming Health Care Quality - Institute of Medicine (The National Academies Press, 2003)
A new release in the Quality Chasm Series, Priority Areas for National Action recommends a set of 20 priority areas that the U.S. Department of Health and Human Services and other groups in the public and private sectors should focus on to improve the quality of health care delivered to all Americans. The priority areas selected represent the entire spectrum of health care from preventive care to end of life care. They also touch on all age groups, health care settings and health care providers. Collective action in these areas could help transform the entire health care system. In addition, the report identifies criteria and delineates a process that DHHS may adopt to determine future priority areas.
Keywords: Health and Medicine

Unequal Treatment: Confronting Racial and Ethnic Disparities in Health Care - Institute of Medicine (The National Academies Press, 2003)
Racial and ethnic disparities in health care are known to reflect access to care and other issues that arise from differing socioeconomic conditions. There is, however, increasing evidence that even after such differences are accounted for, race and ethnicity remain significant predictors of the quality of health care received. In Unequal Treatment, a panel of experts documents this evidence and explores how persons of color experience the health care environment. The book examines how disparities in treatment may arise in health care systems and looks at aspects of the clinical encounter that may contribute to such disparities. Patients' and providers' attitudes, expectations, and behavior are analyzed. How to intervene? Unequal Treatment offers recommendations for improvements in medical care financing, allocation of care, availability of language translation, community-based care, and other arenas. The committee highlights the potential of cross-cultural education to improve provider–patient communication and offers a detailed look at how to integrate cross-cultural learning within the health professions. The book concludes with recommendations for data collection and research initiatives. Unequal Treatment will be vitally important to health care policymakers, administrators, providers, educators, and students as well as advocates for people of color.
Keywords: Health and Medicine

Enhancing the Vitality of the National Institutes of Health: Organizational Change to Meet New Challenges - Institute of Medicine; National Research Council (The National Academies Press, 2003)
The report says that important organizational changes are needed at the National Institutes of Health to ensure the agency meets future challenges effectively. In particular, the report advises NIH to devote additional resources to innovative interdisciplinary research that reflects its strategic objectives and cuts across all agency's institutes and centers. The report recommends that Congress should establish a formal process for determining how specific proposals for changes in the number of NIH agencies and centers should be addressed.
Keywords: Health and Medicine

Leadership by Example: Coordinating Government Roles in Improving Health Care Quality - Institute of Medicine (The National Academies Press, 2003)
The federal government operates six major health care programs that serve nearly 100 million Americans. Collectively, these programs significantly influence how health care is provided by the private sector. Leadership by Example explores how the federal government can leverage its unique position as regulator, purchaser, provider, and research sponsor to improve care - not only in these six programs but also throughout the nation's health care system. The book describes the federal programs and the populations they serve: Medicare (elderly), Medicaid (low income), SCHIP (children), VHA (veterans), TRICARE (individuals in the military and their dependents), and IHS (native Americans). It then examines the steps each program takes to assure and improve safety and quality of care. The Institute of Medicine proposes a national quality enhancement strategy focused on performance measurement of clinical quality and patient perceptions of care. The discussion on which this book focuses includes recommendations for developing and pilot-testing performance measures, creating an information infrastructure for comparing performance and disseminating results, and more. Leadership by Example also includes a proposed research agenda to support quality enhancement. The third in the series of books from the Quality of Health Care in America project, this well-targeted volume will be important to all readers of To Err Is Human and Crossing the Quality Chasm - as well as new readers interested in the federal government's role in health care.
Keywords: Health and Medicine

The Richard and Hinda Rosenthal Lectures 2002: Fostering Rapid Advances in Health Care - Institute of Medicine (The National Academies Press, 2003)
Keywords: Health and Medicine

The Resistance Phenomenon in Microbes and Infectious Disease Vectors: Implications for Human Health and Strategies for Containment: Workshop Summary - Institute of Medicine (The National Academies Press, 2003)
The resistance topic is timely given current events. The emergence of mysterious new diseases, such as SARS, and the looming threat of bioterrorist attacks remind us of how vulnerable we can be to infectious agents. With advances in medical technologies, we have tamed many former microbial foes, yet with few new antimicrobial agents and vaccines in the pipeline, and rapidly increasing drug resistance among infectious microbes, we teeter on the brink of loosing the upperhand in our ongoing struggle against these foes, old and new. The Resistance Phenomenon in Microbes and Infectious Disease Vectors examines our understanding of the relationships among microbes, disease vectors, and human hosts, and explores possible new strategies for meeting the challenge of resistance.
Keywords: Health and Medicine; Food and Nutrition